Social-mediated frame alignment: A study of menstrual activism in China during the COVID-19 pandemic. Issue 3 (3rd July 2022) - Zhou, Qianying; Qiu, Hongfeng; Yang, Xinying
ABSTRACT: At the early stage of the COVID-19 pandemic in China, an urgent appeal for the donation of menstrual products for female medics was ignored by medical institutions. This soon triggered an unprecedented wave of socially-mediated menstrual activism. By adopting frame alignment as a theoretical framework, this study aims to explore the frames social media influencers utilize to represent topics relating to menstruation and menstrual activism and how the public responded on this taboo issue. We conducted a qualitative content analysis of the frames adopted by WeChat posts. Statistical results showed that news organization accounts used fewer conflict, human interest, and feminism frames than individual and corporate accounts in order to avoid controversy in cyberspace. This study also demonstrated the use of frames of menstrual stigma and public invisibility of menstruation was associated with the pro-feminist attitudes of followers, while the use of efficiency and respect frames was correlated with anti-feminist attitudes. These findings should also provide insights into social-mediated frame alignment strategies for future menstrual and other types of activism.